Kearifan Sistem Religi Lokal dalam Mengintegrasikan Umat Hindu-Islam di Bali - I Made Pageh (Department of History, Faculty of Humanities, Diponegoro University, 2018)
This paper aims to gain an understanding of the local religious systems for integrating religious diversity in Bali. This study was conducted using social critical theory. The historical data obtained using literature studies and field research activities. The results of this study indicate that the local religious system in Bali can integrate Hindus and Islam religion. The integration occurs as a result of the relation power that played to integrate national ethnicity in Bali which includes economic interests (trade), and da'wah. The mystical worship and ancestors can approach each other in rituals. The human relations, human and environment relations, human and ancestors occurred harmoniously, not dominating and hegemonic. The cross-cultural integration and multiculturalism formation process has been taken place since the 12th century long before the awareness of Westernization. The integration between villagers in Bali can be used as a model in multicultural education in Indonesia, which today find relevance when various forms of conflict arise based on ethnicity, religion, race, intergroup (SARA). The problem needs to be addressed by fostering national awareness as a whole nation (Austronesian Malay nation)